Foreign Experiences in the Development of the Digital Education System - Ochilova Ozoda Toshkuvvatovna (Open Academia, 2023)
This article explores the digital education system as a way of teaching and using it around the world, digital education, access to quality education, basic foreign experience in improving the education system of countries around the world and developing the digital education system.